Blended Learning Challenges During COVID-19: A Case of Cost Accounting 2 Students at a Selected South African Higher Education Institution - Onke Gqokonqana; Odunayo Magret Olarewaju; Melanie Bernice Cloete (Research in Social Sciences and Technology- OpenED Network, 2022)
Every sector in the twenty-first century makes use of technology for its activities, especially during the COVID-19 pandemic and higher education institutions are not exceptional. However, the cohorts enrolled in the selected higher education institution are from technologically challenged backgrounds. This suggests that in their previous schooling, technology was unemployed as a learning aid. As this may present some challenges for such students, this study aims to investigate challenges experienced by Cost Accounting 2 students who are from a technologically disadvantaged background. To accomplish that, a quantitative approach was used since it permits surveys to be delivered to the entire impacted population while also reducing sampling error. Because of the Coronavirus, online questionnaires were sent to 400 students, but only 119 (n=119) responded. Blended learning was found to be an effective technique for learning Cost Accounting 2 since the university provided sufficient information on how to use the system. However, there was a lot of discussion about internet access, learning materials access, and library resource access. Based on the findings, blended learning is excellent for studying Cost Accounting 2 as long as the learning management system is customised such that students can navigate it effortlessly. Management must work with internet service providers to try stabilise internet connectivity in the students’ neighbourhoods. The additional study can be done using a variety of research methods and target other groups of students.